KONSEP MANUSIA SEMPURNA MENURUT PANDANGAN FRIEDRICH WILLIAMS NIETZSCHE DAN IBNU ARABI; SEBUAH ANALISA KOMPARATIF - Derry Ahmad Rizal (UIN Sunan Kalijaga Yogyakarta, 2020)
This paper aims to do a study of the concept of a perfect human being by taking two corners of the field of characters, Friedrich Williams Nietzsche and Ibn ‘Arabi. In this case the two figures convey their thoughts on how to become perfect human beings. Nietzsche who gives a view about humans must be able, strong and be themselves in facing all their problems. Making humans superior in Netzsche's view. On the other hand Ibn Arabi who explained about the nature of being a perfect human being, and humans themselves are a reflection of the formation of a real God on earth. The level in achieving goals as a perfect human being. The categorization of macrocosm and microcosm in looking at differences in